Utilization of Large-Scale Rolling-Wheel Tester to Investigate the Stress Reduction in Pavement Layers Due to the Use of Geosynthetic Materials. Issue 2 (February 2019) - Wright, Jason; Kim, S. Sonny; Chorzepa, Mi G.; Durham, Stephan A.
In a geosynthetic-reinforced pavement system, the load-bearing capacity of subgrade soil is improved by the lateral distribution of vertical stresses at the reinforcing layer. Under small-scale triaxial testing, the tensile properties of the geosynthetic are difficult to measure. Therefore, it is desirable to conduct large-scale testing to accurately monitor the behavior of geosynthetic-reinforced pavement foundations when subjected to rolling-wheel loadings. This study investigates the behavior of geosynthetic-reinforced pavement foundation systems through large-scale rolling-wheel tests performed with problematic subgrade soils found in north Georgia. Sixteen large-scale specimens were constructed of which twelve were reinforced with geosynthetic. Subgrade soils were compacted either at their optimum moisture content or at a higher than optimum moisture content to produce different California Bearing Ratios during specimen preparation. Both an extruded biaxial geogrid and woven geotextile were placed at various locations to investigate the optimal placement locations for different subgrade conditions. Pressure sensors were installed near the bottom of the aggregate base layer and near the top of the subgrade layer to monitor the variations in vertical stress within the pavement system under rolling-wheel load. Further, light weight deflectometer measurements were collected post-test to determine the effect of the geosynthetic on pavement foundation stiffness. The vertical pressure at the bottom of the aggregate base and top of subgrade decreased on average approximately 15.3% and 18.8%, respectively. The results indicate which type of geosynthetic and placement location provides the greatest reduction of pressure for each of the given subgrade conditions.